ANALISIS PENGUKURAN KUALITAS PELAYANAN KONSUMEN DENGAN METODE SERVQUAL - Dhiana Ekowati; Arsyad Fadhlur Rahman (Jurnal Solusi, 2021)
The hospital is a health institution that is engaged in services. The quality of a service will encourage consumers to form strong bonds with the company. If the service received exceeds consumer expectations, service quality is perceived as ideal quality. Conversely, if the service received is lower than expected, the quality of the service is perceived as poor. Thus, whether the quality of service is good or not depends on the ability of service providers to consistently meet consumer expectations. This study aims to measure the service quality of the Clinical Pathology Laboratory Installation of RSUP Sarjito Yogyakarta using the Servqual Method. The subjects of this study were consumers of the Clinical Pathology Laboratory Installation of the Sarjito Hospital Yogyakarta, while the object of this study was the quality of service for the Clinical Pathology Laboratory Installation of the Sarjito Hospital Yogyakarta. The sample of this research is 99 respondents. The data analysis of this research uses SERVQUAL analysis. The results of this study indicate that the service quality of the Clinical Pathology Laboratory Dr. Sardjito Yogyakarta provides satisfaction to consumers. Keywoard: Quality of Service, SERVQUAL.